Blood Uric Acid in Mild Cognitive Impairment: A Cross-Sectional Study of Older Chinese Adults - Xue L; Xiao X; Mao X; Zhang X; Liu Y; Wu B (Neuropsychiatric Disease and Treatment)
Lingling Xue,1 Xifeng Xiao,1 Xin’e Mao,2 Xiaoli Zhang,1 Yongbing Liu,3 Beibei Wu1 1Department of Nursing, Yangzhou Maternal and Child Health Care Hospital Affiliated to Yangzhou University, Yangzhou, People’s Republic of China; 2Geriatric Unit, Northern Jiangsu People’s Hospital, Yangzhou, People’s Republic of China; 3Department of Nursing, School of Nursing and public Health, Yangzhou University, Yangzhou, People’s Republic of ChinaCorrespondence: Beibei Wu, Yangzhou Maternal and Child Health Care Hospital Affiliated to Yangzhou University, Yangzhou, People’s Republic of China, Email 1128866@qq.comIntroduction: Previous studies focused on the association between uric acid (UA) as an antioxidant and cognitive impairment have been limited in scope and obtained contradictory results. Therefore, we investigated whether low blood UA levels were related to mild cognitive impairment (MCI) in a cross-sectional study.Methods: This study included 231 elderly Chinese adults 60 years and over. We used the MMSE and MoCA to evaluate cognitive function, and fasting venous blood to measure UA concentration. The relationship between blood UA and cognitive impairment was analyzed with multivariate analysis of variance, controlling for demographic information, physical exercise, lifestyle and laboratory results.Results: A total of 90 (38.96%) participants were healthy and 141 (61.04%) had MCI. Compared with the healthy group, MCI patients were more likely to have fewer years of education, inactivity and lower UA levels. UA levels were significantly lower in MCI patients than healthy individuals (P < 0.05). After adjusting for these variables, we found that among MCI patients, lower UA levels were associated with worse cognitive function in the MMSE. Multivariate logistic regression models demonstrated that UA was a protective factor for MCI. Multivariate analysis comparing the high and low quartile group, which was the reference group, indicated that differences in cognition among groups were statistically significant.Conclusion: Lower UA levels were associated with worse cognitive function; therefore, controlling UA levels within a suitable range may slow the progression of cognitive disorders.Keywords: uric acid, mild cognition impairment, factors, differences between groups